Programa de ejercicio físico para estimular la fuerza muscular en adultos mayores del Hogar “Daniel Álvarez Sánchez”, Loja, 2023-2024. - Tenenuela Sarango, Alexis Joel (2024)
The following work on curricular integration was developed with the aim of analyzing the effects of a physical exercise program to stimulate muscle strength in older adults at the "Daniel Álvarez Sánchez" nursing home. In addition, a quantitative methodology was used, with a quasi-experimental and correlational research design. Inductive and deductive reasoning methods were used. Physical evaluation instruments such as the physical test were administered to a sample of 8 older adults. According to the results obtained, once the diagnostic instruments were applied, it is evident that 6 of the 8 participants were at a pre- fragile level. Based on these results, a proposal was designed and applied based on a physical exercise program to stimulate muscle strength in older adults at the “Daniel Álvarez Sánchez” nursing home, which was structured in 3 sessions per week for a period of 2 months. training with exercises focused on stimulating muscle strength. After that, control instruments were applied where progress in the mentioned aspects was evident. It is concluded that before the application of the proposal there were certain limitations in aspects of muscle strength and movement on the part of older adults, however, when applying the post-test these aspects improved considerably, going from 1 participant to 4 in entering the autonomous level, thus demonstrating the effectiveness of the physical exercise program to stimulate muscle strength. Keywords: physical exercise, muscle strength, older adults, physical test and physical evaluation.